2015
DOI: 10.1021/acs.jpca.5b09871
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Spin Competition in Small-Sized Al Clusters

Abstract: Stern-Gerlach (SG) experiments on aluminum clusters indicate that some small-sized aggregates exhibit a deflection signal consistent with the existence of magnetic moments. However, in the particular case of Al6 and Al8 clusters, electronic structure investigations show ambiguity on the 0 K ground spin state. In this work extensive computations of the electronic structure have been carried out in order to determine the ground state of these structures. Electron correlation has been introduced at MP2, MP4, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…We have built the global minimum structures of Al nanoclusters up to Al 12 with PyAR|XTB, and up to Al 8 with PyAR|BP86. There are several theoretical studies on Al clusters at various levels of theory, such as Sutton-Chen empirical potential (Joswig and Springborg, 2003), DFT (Ahlrichs and Elliott, 1999; Rao and Jena, 1999), and CCSD(T) (Shinde and Shukla, 2014; López-Estrada and Orgaz, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…We have built the global minimum structures of Al nanoclusters up to Al 12 with PyAR|XTB, and up to Al 8 with PyAR|BP86. There are several theoretical studies on Al clusters at various levels of theory, such as Sutton-Chen empirical potential (Joswig and Springborg, 2003), DFT (Ahlrichs and Elliott, 1999; Rao and Jena, 1999), and CCSD(T) (Shinde and Shukla, 2014; López-Estrada and Orgaz, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Al 2 has been observed to have two local minima both experimentally 91 and theoretically. 92 The spectroscopy experiment reports a 3 ∏ u electronic ground state with a bond length of 2.7011 ± 0.0015 Å and a vibrational frequency of 285.80 cm –1 . Similarly, a 3 ∑ g – electronic state with a bond length of 2.4665 ± 0.0024 Å and a vibrational frequency of 350.01 cm –1 has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…85,90 In such an attempt, we discuss the error of employing the distinct averages in a model system of an aluminum dimer, which has been extensively investigated both experimentally 91 and theoretically. 92 This simple model, while not an ET system, allows us to explore analytically the reorganization energies as well as the driving force by noting that the Marcus−Hush theory can be seen as a method to find the intersection between the parabolas along the reaction coordinate. The analysis of the relative error allows us to explore novel donor and acceptor molecules used in organic photovoltaics by means of the averaged reorganization energy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14 The structure, and electronic and magnetic properties of small free and supported Cr and other transition metal magnetic clusters have been extensively investigated experimentally [15][16][17][18][19] and theoretically. [20][21][22][23][24][25] There has been found a strong interplay between the atomic structure and magnetic order in the clusters. Thus, for Cu(111) surface supported small clusters of Fe, Mn, and Cr it has been revealed that the Fe clusters show ferromagnetic order regardless of the cluster geometry.…”
Section: Introductionmentioning
confidence: 99%